Mitigation Literacy of Fire Disaster for Early Childhood by Integrating Islamic Values - Dinar Nur Inten; Dewi Mulyani; Arif Hakim (Jurnal Pendidikan Islam Indonesia, 2022)
This research departs from our concern as researchers about the various disasters that have occurred in our beloved country, as well as our concern for the future of the children affected by the disaster. Therefore, with the aim that early childhood literate and aware of the causes of disasters, as well as avoiding disasters that occur and dealing with disasters that occur, our research on disaster mitigation literacy for early childhood carried out by integrating three fun learning methods and integrating Islamic values. The disaster theme raised was the theme closest to children, namely fire. This study used a classroom action research method. The subjects were early childhood education children at Ar-Rahman school in the city of Bandung. The lesson began by explaining the concept of fire by integrating Islamic values, such as verses, hadiths and mahfudzot related to disasters. Furthermore, materials strengthening was implemented with various activities that involved children. In addition, at the peak of fire simulation, activities were also carried out. The results showed that disaster mitigation through literacy for early childhood on the theme of fire, by integrating Islamic values ​​and involving children in learning, made children more sensitive to disasters, knew how to take action to prevent disasters from happening, knew the stages when facing fires, so that they can save themselves and become grateful servants of God.